MENINGKATKAN KEMAMPUAN GURU DALAM MENGELOLA KELAS MELALUI SUPERVISI AKADEMIS DI SMA NEGERI 76 JAKARTA - Sukarmo Sukarmo (Program Studi Manajemen Pendidikan, 2019)
This research is a class action study conducted at SMA Negeri 76 Jakarta, this research aims to improve the teacher's ability to manage classes through academic supervision. This research is a qualified method research with the design of the research action used in this research is the Hopkins model. The research instrument as a data collection tool in the study is an observation sheet in the form of rubric, poll, interviews, documentation studies, and library studies. Observation, used to collect data about teacher activity in learning activities. The results of the study were divided into two cycles i.e. cycle I and II, in cycle I based on the results of the average score from eleven respondents showed still not optimal levels of the teacher's ability to manage classes. This is evident from the average observation score of 3.09 and the average value of the poll is 3.12 from the maximum score of 4.00. While in cycle II the average score from respondents showed an increase when compared to gains in cycle I. This is evident from the average observation score of 3.65 and the average value of the poll is 3.64.